MEDIA KONKRIT SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN OPERASI PERHITUNGAN SISWA KELAS I SD NEGERI 001 RANAI - Ermawati Ermawati (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2023)
This study aims to improve students' ability to operationalize addition and subtraction in mathematics using concrete media in class I SD Negeri 001 Ranai, Bunguran Timur District, Natuna Regency. The data in this study were obtained from interviews, action observations, and evaluation results. This research was conducted in two cycles. Each cycle is carried out based on the stages: (1) preparing an activity plan, (2) carrying out actions, (3) observing, and (4) analyzing followed by reflection. The results of the research on pre-action scores > 77 were 43% of all students and scores <77 were 57% of all students. The researcher took the KKM standard score of 77, because the value of 77 is above the sufficient value for learning success. Then after the action was taken, from the results of the learning evaluation in cycle I with the lowest standard value of 77, students who obtained a score > 77 were 19 students out of 21 students, namely 90% while the results of the evaluation in cycle II with the same standard value, all students obtained a value > 77 or 100 %.